Kompetensi Organisasi : Studi Literature - Siti Khotijah; Badrussholeh; Moch. Isa Anshori (CV. Aksara Global Akademia, 2023)
Organizational competence refers to the pool of knowledge, skills, resources and capabilities that an organization has to achieve its strategic goals. Where at this time the organization operates in an increasingly complex and rapidly changing environment. With this in mind, in the ever-evolving business world, it is important for organizations to understand and develop competencies in order to be able to face challenges and obstacles that continue to arise. This study uses the method of literature study. The results obtained are that the development of appropriate organizational competencies can provide benefits such as better adaptation to changes in the innovation environment that are more effective, and to achieve competitive advantage organizations need to understand their business context and identify the most relevant and effective basic competency components in achieving strategic goals. they.